The state of fundraising within the nonprofit social service sector : a study to determine how and to what levels of success South African NPOs are managing and operating their fundraising functions - Kilbey, Brian (Department of Social Development, 2015)
This study sought analyse the state of fundraising within the South African nonprofit social service sector at the end of the 2007/2008 financial year. The overall aim of the study was to evaluate the fundraising capacities of social service organisations, in order to ascertain whether organisations were proficient in their fundraising-related activities.